SOSIALISASI PELAKSANAAN KEGIATAN DESTINATION BRANDING SECARA DIGITAL BAGI MASYARAKAT KAMPOENG PINTAR OASE TEMBOK GEDE RT 03 RW 02 KELURAHAN BUBUTAN KECAMATAN BUBUTAN - Nalendra, Irham Wahid; Rahayu, Salsabila Putri; Maharani, Dian; Nusantara, Mhd Dharma Samudra; Rahmatin, Leily Suci (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Digital transformation has become a crucial necessity in developing regional potential, particularly in strengthening image and competitiveness in the information technology era. Kampoeng Pintar Oase Tembok Gede, a thematic village in Surabaya, holds great potential in MSMEs, educational tourism, and environmental innovation. However, the lack of public knowledge and skills in utilizing digital tools poses a significant barrier to effective branding efforts. Through an outreach program titled “Effective Digital Branding Strategies”, the SDGs Community Service Team (KKN) Group 2 from UPN Veteran East Java aimed to educate local residents about the importance of building a digital identity via social media platforms. The service method involved problem identification through interviews and field observation, planning educational materials and strategies, conducting participatory sessions, and performing evaluation through feedback and group discussions. The results indicated a high level of enthusiasm and active involvement from participants, who gained new insights into the fundamentals of digital branding, implementation strategies, and basic promotional content creation. The program successfully increased community awareness of the role of digital media in promoting local potential. Future recommendations include continuous follow-up in the form of technical training, mentoring in content creation, and the establishment of a village digital community hub for sustained digital literacy and branding efforts.activities such as technical training and digital mentoring are recommended to help establish a self-sustaining digital community in the area.